Peningkatan Perilaku Kesehatan Gigi dan Mulut Anak Tunarungu Menggunakan Media Pop-up - Syamsuddin Abubakar; Muhammad Saleh; Rini Irmayanti Sitanaya; Amelya Tiara Diva (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2026)
Oral and dental health among deaf children deserves particular attention, since their communication limitations often make it difficult for them to grasp proper oral hygiene practices. A pop-up book is one educational medium suitable for this purpose, given its visual, attractive, and easy-to-understand nature. This study examined the extent to which preventive and promotive activities using pop-up media could improve oral and dental health behavior among deaf children at SLB Negeri 1 Makassar. A quasi-experimental design with a one-group pre-test post-test approach was applied. Forty deaf students were involved as the sample through a total sampling technique. Data were gathered using questionnaires, observation, and oral hygiene index examinations (OHI-S). Since the data were not normally distributed, the Wilcoxon test was used for analysis. Findings revealed improvement across all measured aspects following the intervention. The proportion in the good category rose from 15% to 72.5% for knowledge, from 22.5% to 72.5% for attitude, from 17.5% to 87.5% for action, and from 22.5% to 82.5% for OHI-S status. The Wilcoxon test produced a significance value of p=0.000 (<0.05) across all variables, indicating a genuine improvement in oral and dental health behavior following pop-up-based education. It can therefore be concluded that pop-up media serves as an effective preventive and promotive tool for enhancing oral and dental health behavior among deaf children.